Reformulasi Tindak Pidana Perzinahan Dalam Sistem Hukum Pidana Indonesia - Pahrur Rizal (Jatiswara, 2017)
Sex is a act that can make disturbing of importance balance in living society. Sex of criminal act have arranged in law dictionary of Indonesia, but isn’t fill moral values alive. In 284 KUHP section just arrange sex who to do by some one of still bunch of marriage. The consept in KUHP about sex is different with the living norm in Indonesia society that assumption of sex is copulation by the men or women who isn’t bunch of marriage. The use of method is research of legal formal. Subsequently, the research use law approach and concept approach. The result to the processed use invention of law, it mean examine living law in Indonesia society. Then, analyzed and concluded by deductive think. The resulting of research conclude that application of criminal law about morality act (sex) can be applied very well if always to consider values of law or norms that living in society. There for, repair Indonesia criminal law can to do by integrate all culture value that grow in Indonesia society.